Bioinformatics, bacterial expression and enzyme activity analyses of dichloromethane dehalogenase from Methylobacterium rhodesianum H13. Issue 1 (1st January 2020) - Ni, Jianguo; Liu, Ying; Shen, Chenjia; Chen, Dongzhi; Xin, Yueyong; Liu, Qi
Abstract: Dechlorination is the key step in biological degradation of dichloromethane (DCM), which is catalyzed by the enzyme DCM dehalogenase. In this study, the detailed structure and function of DCM dehalogenase in Methylobacterium rhodesianum H13 were investigated. Our results indicate that DCM dehalogenase (C1505H2255N403O430S7) is a stable hydrophilic protein localized in the cytoplasm, with an isoelectric point of 6.35. They also indicate that DCM dehalogenase is a frizzled protein with 52.43% of amino acid residues exposed on its surface, and that alpha-helices are a main structural component (53.47%). As one of the theta class glutathione S-transferases (GSTs), DCM dehalogenase presents as a dimeric structure and shows strong substrate selectivity. The catalytic tunnel radius and length of DCM dehalogenase are both 1.4 Å. Glu42 and Val43 are two of the essential amino acids in both the catalytic tunnel and catalytic pockets. The amino acid sequence of DCM dehalogenase was predicted to be homologous among various microorganisms, and its active site was conserved with eight potential sites. The recombinant DCM dehalogenase was expressed in E. coli BL21 strain. The optimum conditions for DCM dehalogenase are pH 8, temperature of 30 °C and presence of Mn 2+ . All the obtained information of DCM dehalogenase will lay the foundation for further study of its structural transformation and functional improvement.